2022
DOI: 10.3390/jrfm15070287
|View full text |Cite
|
Sign up to set email alerts
|

Fintech Innovations in the Financial Service Industry

Abstract: Digital transformation underscored by the fourth industrial revolution has led to the emergence of sophisticated technology-enabled financial services known as fintech, that has swiftly altered traditional financial services space. Global adoption of fintech is rapidly increasing due to its disruptive nature and is largely embraced by participants who are underserved by traditional financial service providers. Global investments in fintech are growing rapidly year by year owing to increased interconnectivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 112 publications
1
19
0
1
Order By: Relevance
“…FinTech payments encompass cutting-edge and technology-fueled approaches that streamline the movement of monetary assets and improve the effectiveness of financial transactions through digital procedures and tools. The financial technology sector has made significant advancements that have revolutionized payment systems, providing accelerated, secure, and convenient alternatives to conventional payment methods (Anifa et al, 2022). Recent research has shown that the adoption of FinTech payment solutions is influenced by several factors, such as user-friendliness, convenience, and perceived security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…FinTech payments encompass cutting-edge and technology-fueled approaches that streamline the movement of monetary assets and improve the effectiveness of financial transactions through digital procedures and tools. The financial technology sector has made significant advancements that have revolutionized payment systems, providing accelerated, secure, and convenient alternatives to conventional payment methods (Anifa et al, 2022). Recent research has shown that the adoption of FinTech payment solutions is influenced by several factors, such as user-friendliness, convenience, and perceived security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, they have become profit-focused, and the cost of loans for poor borrowers has risen considerably (Bardhan et al, 2021). The recently launched fintech firms in India have been offering loans using a more customer-focused approach (Anifa et al, 2022). Financial inclusion also leads to social inclusion, and p2p lending can bridge the gap in access to microcredit that the banks and other financial services players are unable to fulfil (Maity, 2023).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…, 2021). The recently launched fintech firms in India have been offering loans using a more customer-focused approach (Anifa et al. , 2022).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…Commercial banks use cutting-edge technologies to aggregate relevant information from multiple perspectives, thereby enriching the types and content of risk information. The in-depth integration of emerging technologies such as machine learning, artificial intelligence, and the financial industry revolutionized traditional bank risk management (Anifa et al 2022, Cheng and Qu 2020, Lagna and Ravishankar 2022.…”
Section: Technology Spillover Effectmentioning
confidence: 99%